Cley Hill
This is one of hill forts constructed by the Iron Age people, who seem to have lived in troubled times. Their hilltops, ridgeways, and earthworks are defensive in attitude, and there is little evidence of building in any durable material. However, their successors, the Celtic people, left a heritage of poetry and art which remains alive, especially in Wales and Ireland, to this day.